Accelerometric analysis of trunk acceleration during gait analysis in children between 6 and 11 years old: A cross-sectional study - Jesús García-Liñeira; Raquel Leirós-Rodríguez; Vicente Romo-Pérez; Jose L. García-Soidán (Heliyon, 2023)
Background: Gait analysis in children with accelerometers is of special interest in daily clinical practice, as it eliminates possible biases related to the assessor and is not very sensitivity of visual analysis. The sensitivity of data collection by these instruments makes it possible to evaluate the efficiency of body movements during gait and to better understand the degree of motor development in childhood, assessing progress within normal developmental parameters or detecting possible deficits. Research question: What are the accelerations of the center of mass during normal gait in children aged 6–11 years? Methods: Descriptive cross-sectional study conducted with a total of 283 school children (girls = 142). The analyzed variables were the mean and maximum values obtained in each of the three body axes and their root mean square during normal gait 10 m out, turn and 10 m back over firm ground in a straight line three times. Results: The accelerometric data obtained showed similar values between sexes in each of the age sub-groups analyzed. Except for the medial-lateral axis in children aged 10–11 years where differences between sexes were detected (being significantly lower in girls). A reduction in medial-lateral axis average values over the years was also identified in both sexes. The regression models generated for the average accelerometric values showed significant values only in the average value of the medial-lateral axis. However, the maximum values were significant in all cases. Significance: The preferred motor strategies of boys and girls during gait include developing mainly control and adjustment movements in the frontal plane (hence the high magnitudes recorded there). Flexion-extension movements are the most reduced over the six years of age analyzed, particularly in girls. Conversely, rotational movements are the most constant in speed in both sexes and all age subgroups.